RESIDUAL STRESS ANALYSIS OF INSULATION COATINGS FOR MAGNET TECHNOLOGIES - Guney, D. (POLISH ACAD SCIENCES COMMITTEE METALLURGY, 2013)
High temperature MgO-ZrO2 insulation coatings were grown on long-length Stainless-Steel (SS) tapes by reel-to-reel sol-gel method for applications of High Temperature Superconductor/Low Temperature Superconductor (HTS/LTS) coils and magnets. The residual stresses were investigated analytically at various temperature ranges, 580 degrees C to 25 degrees C (room temperature) and -196 degrees C (liquid helium temperature), and 630 degrees C to 25 degrees C and -196 degrees C for different thicknesses to be 13, 12, and 7 mu m. The maximum stress values were obtained to be 1.92 GPa in tension for SS substrate with the 13 mu m coating and -2.42 GPa in compression for the 7 mu m MgO-ZrO2 coating in the temperature range between 630 degrees C and liquid helium temperature. The surface morphologies and microstructure of sample were also characterized using a scanning electron microscope (SEM). SEM observations revealed that MgO-ZrO2 coatings have a mosaic like crack structure.
Keywords: residual stress; sol-gel; MgO-ZrO2; insulation and superconducting magnet; THIN-FILMS; TEMPERATURE; TAPES; Metallurgy & Metallurgical Engineering